1
$\begingroup$

Q: $x^2y^{''}-(x^2+2)y=0$ [1]

Solving using frobenius

$y=\sum_{n=0}^{\infty}a_nx^{x+r}$ [2]

$ y'=\sum_{n=0}^{\infty}(n+r)a_nx^{x+r-1}$ [3]

$ y''=\sum_{n=0}^{\infty}(n+r)(n+r-1)a_nx^{x+r-2}$ [4]

inserting [2,4] into [1]

$x^2 \sum_{n=0}^{\infty}(n+r)(n+r-1)a_nx^{x+r-2}-(x^2+2)\sum_{n=0}^{\infty}a_nx^{x+r}$ [5]

Multiplying through but the cofficent I get

$\sum_{n=0}^{\infty}(n+r-1)(n+r)a_n x^{n+r}-\sum_{n=0}^{\infty}a_nx^{x+r+2}-2\sum_{n=0}^{\infty}a_nx^{n+r}$

setting n=0 I solve for r to get the values of $r=2 , r=-1$

Now this is where my confusion comes in

so for r=2 I rearnage the series like so

$x^2(\sum_{n=0}^{\infty}[(n+r-1)(n+r)a_n -2a_n]x^{n}-\sum_{n=0}^{\infty}a_nx^{n+2})=0$ [6]

So now what I did I want all x's to be of the same power so I did the following:

$k=n+2$

$k-2=n$

$\sum_{k=0}^{\infty}[(k+1)(k+2)a_n -2a_k]x^k-\sum_{k=2}^{\infty}a_{k-2}x^k=0$ [9]

expanding on the series $\sum_{k=0}^{\infty}[(k+1)(k+2)a_n - 2a_n]x^k$ so I can get the staring point of the series in the same postion I did the following

$k=0, 2a_0-2a_0=0 \rightarrow a_0=0$

$k=1, 6a_{1}-2a_{1} \rightarrow a_1=0$

$a_0=a_1=0$ is because [9] is equal to $0$

so now I have the equation

$\sum_{k=2}^{\infty}[(k+1)(k+2)a_n - 2a_n-a_{k-2}]x^k=0$

So I now have a recurrence relation of:

$(k+1)(k+2)a_n - 2a_n-a_{k-2}=0$

$a_n=\frac{a_{k-2}}{k(k+3)}$

Now in my book solution it has the solution of

$a_2=\frac{a_0}{2\cdot 5}$ $a_3=0$ $a_4=\frac{a_0}{2\cdot 5\cdot 4\cdot 7}$

but how is it $a_0$? I know I have gone somewhere wrong but just cant see where.

$\endgroup$
3
  • $\begingroup$ Without initial values you should have $2$ arbitrary constants $\endgroup$ – Raffaele Oct 31 '17 at 20:06
  • $\begingroup$ I am not understanding by what you mean by initial values $\endgroup$ – Jason Taylor Oct 31 '17 at 20:25
  • $\begingroup$ @JasonTaylor: There are some typos in mixing up $x$ with $n$ e.g. $x^{x+r}$ instead of $x^{n+r}$ and mixing up $n$ with $k$. You might want to check the question and correct it by yourself. This might be in connection with the mistake I've addressed in my answer. I have the impression that your understanding is quite good, but there are a lot of slips of the pen which may cause sometimes problems. $\endgroup$ – Markus Scheuer Nov 1 '17 at 13:58
1
$\begingroup$

Your approach is fine. There is just a small mistake which causes the problem. In the following we use the coefficient of operator $[x^k]$ to denote the coefficient of $x^k$ in a series.

Let's consider again the series equation \begin{align*} \sum_{k=0}^\infty[(k+1)(k+2)a_k-2a_k]x^k-\sum_{k=2}^\infty a_{k-2}x^k=0\tag{1} \end{align*}

We consider the coefficient of $x^0$ \begin{align*} [x^0]:\qquad 2a_0-2a_0=0\qquad \text{resp.}\qquad 0=0 \end{align*}

We observe this equation provides no information at all. So $k=0$ can't be usefully used (this was the mistake) and $a_0$ is left unspecified. This becomes plausible, when we rearrange the equation (1) somewhat. We obtain \begin{align*} \sum_{k=0}^\infty&[(k+1)(k+2)a_k-2a_k]x^k-\sum_{k=2}^\infty a_{k-2}x^k\\ &=\sum_{k=0}^\infty(k+3)ka_kx^k-\sum_{k=2}^\infty a_{k-2}x^k\tag{1}\\ &=\sum_{k=1}^\infty(k+3)ka_kx^k-\sum_{k=2}^\infty a_{k-2}x^k\tag{2}\\ &=0 \end{align*}

Comment:

  • In (1) we simplify $(k+1)(k+2)a_k-2a_k$ and observe the coefficient $a_0$ vanishes in the left-hand series since $(k+3)k=0$ if $k=0$.

  • In (2) we can therefore start the left series with $k=1$.

From (2) we obtain the expected relations: \begin{align*} [x^1]:\qquad &&4a_1&=0&\qquad &\color{blue}{a_1=0}\\ [x^2]:\qquad &&10a_2-a_0&=0&\qquad &\color{blue}{a_2=\frac{a_0}{10}}\\ [x^3]:\qquad && 18a_3-a_1&=0&\qquad &\color{blue}{a_3=0}\\ [x^4]:\qquad &&28a_4-a_2&=0&\qquad &\color{blue}{a_4=\frac{a_2}{28}=\frac{a_0}{280}} \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.